Macroeconomic and demographic impacts on Islamic life insurance demand in Indonesia - Tilova, Tari Yulia; Wiliasih, Ranti; Nursyamsiah, Tita (Faculty of Economics, Universitas Islam Indonesia, 2025)
Purpose – This study examines the influence of macroeconomics and population demographics on demand for Islamic life insurance in Indonesia.Methodology – This study uses time-series data analysis using the autoregressive distributed lag (ARDL)method. The study period is from January 2015 to December 2022.Findings – According to the ARDL model, inflation and education levels have a positive effect on the demand for Islamic life insurance in the long run, while the Muslim population has a negative effect. In the short term, gross domestic product (GDP) per capita has a positive effect, while inflation and the Muslim population have a negative effect on the demand for Islamic life insurance in Indonesia.Implications – This study provides valuable insights for the Islamic life insurance industry and policymakers. The industry should develop inclusive and affordable products tailored to diverse financial capacities and preferences, including those of the younger generations. Policymakers should promote public awareness and collaboration with financial institutions in order to expand access. These findings can guide strategies to enhance market penetration and financial inclusion.Originality – This study fills the research gap by analyzing the relationship between Islamic life insurance demand, macroeconomics, and population demographics, where Muslim population has never been discussed by previous studies.